Integrating Cultural and Religious Values in Education: A Web-Based Approach to Promoting Social Awareness in Islamic Schools - S Syaharuddin; M Mutiani; Sovia Husni Rahmia; Fatwa Nur'aini; Aay Susilawati (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
The integration of social studies and religious education is essential to foster social awareness among Madrasah Aliyah students. This study investigates the effectiveness of the web-based Cultural Religious Integration Model (CRIM) application in enhancing students’ social awareness. A qualitative descriptive approach was used, involving 64 twelfth-grade students from two Islamic institutions in Indonesia: MA Sirnamiskin Bandung (n=20) and MAN 2 Banjarmasin (n=44). The students’ social awareness was evaluated based on five key indicators: tolerance for differences, cooperation in diversity, respect for traditions and cultures, communication etiquette, and active participation in promoting social harmony. The results indicated that the CRIM application significantly improved social awareness, with students from both institutions achieving “very good” ratings on all indicators. The application, which utilizes real-life scenarios and interactive learning activities, facilitated students’ understanding through discussions, case studies, and projects. This study contributes to the expanding field of technology-enhanced religious education, offering valuable implications for the development of inclusive educational models in Islamic schools. Future research should explore expanding the CRIM application’s functionality and assessing its effectiveness in various educational settings to further enhance its impact on social awareness.